2011
DOI: 10.1002/adma.201100310
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Walled Carbon Nanotube Aerogel‐Based Elastic Conductors

Abstract: Flexible conductors of various shapes and sizes with high electrical stability under large elastic stretching and bending are of significant importance in diverse fields ranging from microelectronics to biological implants. Stretchable conductors are fabricated by completely backfilling single‐walled carbon nanotube aerogels with elastomeric polymers. The resistance of the stretchable conductors remains nearly unchanged under tensile strain and high bending strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
194
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 31 publications
6
194
0
Order By: Relevance
“…During the first cycle of stretchingreleasing, the resistance of p-BC/PDMS composite increased nearly linearly with increasing tensile strain (Figure 3a). The resistance increase (DR/R 0 ) at the maximum strain (80%) is 14.8%, which is much lower than the reported values for conventional graphene-and CNT-based stretchable conductors 2, 10,11,18 and is comparable to that of emerging single-walled carbon nanotubes/PDMS 21 and graphene foam/PDMS 22 composites. When the stretched composite was released to the unstrained state, we observed 9.2% loss in conductivity, implying a partial breaking or cracking of the nanofibrous network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the first cycle of stretchingreleasing, the resistance of p-BC/PDMS composite increased nearly linearly with increasing tensile strain (Figure 3a). The resistance increase (DR/R 0 ) at the maximum strain (80%) is 14.8%, which is much lower than the reported values for conventional graphene-and CNT-based stretchable conductors 2, 10,11,18 and is comparable to that of emerging single-walled carbon nanotubes/PDMS 21 and graphene foam/PDMS 22 composites. When the stretched composite was released to the unstrained state, we observed 9.2% loss in conductivity, implying a partial breaking or cracking of the nanofibrous network.…”
Section: Resultsmentioning
confidence: 99%
“…11,19 Although mechanical stretchability was successfully achieved, most of the above studies demonstrated that the resistance of the obtained composites increases rapidly with tensile strain (4100% increase of resistance at 100% strain). 5,10,11,17,18 Very recently, a new strategy was developed for generating stretchable conductors by backfilling an infinite connected network of conducting fillers (such as single-walled carbon nanotubesaerogels 21 or graphene foams 22 ) with an elastic polymer. Owing to the prefabricated three dimensional (3D) network structures, these composites showed a relatively high electrical conductivity and electromechanical stability under stretching and bending.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…One example would be the fabrication of nanocomposites using the previously reported CNT aerogel architecture, 16,[29][30][31] but due to the small pore sizes in CNT aerogels, 29 the infusion of matrix materials into such architectures usually requires a pressure differential that may damage the very fragile CNT network. Another problem of polymer nanocomposites formed using unaligned CNTs is that a uniform dispersion of CNTs leads to isotropic nanocomposite properties, which cannot be optimized for any single operating direction.…”
Section: 20mentioning
confidence: 99%
“…1,2, 8,[11][12][13][14][15][16][17] To take full advantage of the anisotropic properties, a number of recent studies focused on the integration of aligned carbon nanotubes (CNTs) at a variety of CNT volume fractions (V f ) into a polymer matrix architecture, [18][19][20][21][22] forming an aligned CNT polymer nanocomposite (A-PNC). However, due to the limitations of sample size and testing techniques, which commonly include either bulk compression or nanoindentation, [18][19][20] previous studies were not able to determine the full constitutive relations for such materials.…”
Section: Introductionmentioning
confidence: 99%